Hantaan virus infection induces human mucosal-associated invariant T cell pyroptosis through IRE1α pathway - Yusi Zhang; He Liu; Dalu Liu; Huiyuan Zhang; Ying Ma; Na Li; Chunmei Zhang; Manling Xue; Fenglan Wang; Xiaozhou Jia; Hui Zhang; Kang Tang; et al. (Communications Biology)
Abstract Hantaan virus (HTNV) triggers an epidemic of hemorrhagic fever with renal syndrome (HFRS), which is predominantly prevalent in Asia. Mucosal-associated invariant T (MAIT) cells, categorized as innate-like T lymphocytes, perform crucial functions in the innate host defense mechanism during virus infection. We previously showed that MAIT cells played antiviral roles in vitro. But marked reduction of MAIT cells was present in the peripheral blood of HFRS patients. Till now, the role of MAIT cells in vivo and the mechanisms of HTNV-induced the MAIT cell deficiency have not yet been fully explored. In this study, by combining the clinical samples, MAIT deficiency mice and in vitro infected MAIT cell models, we find that pyroptosis was the main reason of MAIT cell loss in the peripheral blood of HFRS patients. The molecular mechanisms are related to the overload of calcium in the endoplasmic reticulum (ER) of MAIT cells, which subsequently induces inosital-requiring enzyme-1α (IRE1α)-mediated ER-stress and following pyroptosis. ER-stress inhibitor can reverse the pyroptosis of MAIT cells during HTNV infection. In conclusion, this study firstly reveals the underlying molecular mechanisms for the deficiency of MAIT cells during HTNV infection, and suggests a potential way to stabilize the MAIT cells population in HFRS.